IN VITRO IRON AVAILABILITY AND ADSORPTION PATTERN ON COMBINATION OF ACIDITY AND LENGTH OF BOILING TIME ON YARD LONG BEAN - Leny Yuanita (Indonesian Journal of Chemistry, 2005)
The aim of the study is to find iron availability and binding pattern by dietary fiber macromolecule on combination of acidity and length of boiling time, through Kads and Keff, boiling procees at the level of pH 4 and 7 with boiling time at 0 (raw), 5, 15, and 25 minutes. Iron availability and adsorption pattern were analyzed through Miller's in-vitro and Langmuir-Scatchard graph methods. The results of the study showed: (1) the highest iron availability occurs at raw-pH4 treatment; (2) decreasing pH and increasing boiling time decrease Kads,Keff, percent iron bound, and increase iron availability; (3) iron binding pattern by dietary fiber macromolecules through formation of complex compound was more prominent than physical adsorption, involving two types of specific binding sites, one of which showed a higher affinity.